2003
DOI: 10.1080/10473289.2003.10466307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO2 on Immobilization of Metals and Encapsulation of a Glass Network in Slag

Abstract: The final disposal of ash from an incinerator is of special concern because of the possibility of its releasing toxic substances. Melting/vitrification has been regarded as a prospective technology of ash treatment. The object of this investigation was to evaluate the effect of silica (SiO 2 ) addition on the immobilization of hazardous metals and the encapsulation of a glass network during the vitrification process. Four specimens with SiO 2 /fly ash mixing ratios of 0, 0.1, 0.2, and 0.3, respectively, were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…The high degrees of volatilization observed for Cd (≥ 73.4%), Pb (≥ 79.1%) and Zn (≥ 87.9%) shown in Tables 4-6 are in agreement with studies of other authors reporting high emissions of these metals even at lower temperatures [1,28,29]. Moreover attempts made by Tang et al [29] to reduce the emission levels during incineration by using hydroxyapatite didn't provide the desired results for zinc.…”
Section: Cadmium Lead and Zincsupporting
confidence: 80%
See 2 more Smart Citations
“…The high degrees of volatilization observed for Cd (≥ 73.4%), Pb (≥ 79.1%) and Zn (≥ 87.9%) shown in Tables 4-6 are in agreement with studies of other authors reporting high emissions of these metals even at lower temperatures [1,28,29]. Moreover attempts made by Tang et al [29] to reduce the emission levels during incineration by using hydroxyapatite didn't provide the desired results for zinc.…”
Section: Cadmium Lead and Zincsupporting
confidence: 80%
“…The lowest emission levels of 9.5 ± 6.5% (SS2-FA), 13.2±8.1 (SS1F-FA3) and 13.4 ± 1.3% (SS1P-FS) seem to be in line with Kuo et al [28] who reported low volatilization of this metal when vitrifying MSW fly ash. …”
Section: Nickelsupporting
confidence: 74%
See 1 more Smart Citation
“…The Pb and Zn contents were extremely high in comparison to those in the incinerator ash, implying that recovering by acid or alkaline leaching deserves consideration [15,16]. Both metals can also be reconcentrated to higher levels by recycling the fly ash into the furnace for more economical recovery [10].…”
Section: Resultsmentioning
confidence: 98%
“…In our previous work, the mobility and encapsulation of metals during a lab scale vitrification was studied, but the behavior of metal species was not investigated [10]. In this study, metal mass fluxes of input and output material during vitrification of incinerator ash in such a system were estimated.…”
Section: Introductionmentioning
confidence: 98%